In vitro evaluation of antioxidant and neuroprotective effects of berberine loaded in nanostructured lipid carriers - Radostina Bogdanova; Magdalena Kondeva-Burdina; Teodora Popova; Borislav Tzankov; Christina Voycheva; Marta Slavkova; Virginia Tzankova; Denitsa Stefanova (Pharmacia, 2025)
Berberine (BRB) is a natural alkaloid with diverse pharmacological properties, including antitumor, anti-inflammatory, and glucose-lowering effects. Recently, its neuroprotective potential has garnered attention due to its role in mitigating oxidative stress, protein aggregation, and inflammation – key factors in neurodegenerative diseases. However, BRB’s therapeutic application is limited by poor solubility, low bioavailability, and extensive metabolism. To address these challenges, nanotechnology-based drug delivery systems have been explored. Among them, nanostructured lipid carriers (NLCs) offer an attractive strategy due to their biocompatibility, high drug loading capacity, and ability to enhance BRB’s solubility and stability. Additionally, intranasal administration of NLCs could facilitate direct nose-to-brain delivery, bypassing systemic metabolism and reducing potential side effects. The aim of this study was to develop and characterize a nanostructured lipid carrier formulation incorporating BRB (NLC-B) to enhance its solubility and neuroprotective effects. The physicochemical stability of the NLC-B system was assessed, and its ability to retain BRB’s antioxidant and neuroprotective properties was evaluated using various in vitro models. These included a 6-hydroxydopamine-induced neurotoxicity model in isolated rat brain synaptosomes, a tert-butyl hydroperoxide-induced oxidative stress model in isolated rat brain mitochondria, and an iron/ascorbate-induced lipid peroxidation assay in isolated rat brain and liver microsomes. The findings from this study provide insights into the feasibility of NLC-B as a promising drug delivery system for enhancing the therapeutic potential of berberine in neurodegenerative disease treatment.